The Perennialism Approach toward the Unity of Religions - Adi, Brian Trinanda Kusuma (Fakultas Ushuludin Adab dan Humaniora Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri, 2023)
The formation of a sound interreligious dialogue concept is essential if different religious believers are to coexist peacefully. Many well-known religious experts have been working very hard to establish a foundation for interreligious discussion. Some of them have made an effort to conceptualize the notions of religious unity, in which all the many religions in this multireligious world could find common ground. placed. Let's start by looking at how people now interact with religion. People who argue that all religions' teachings are relative reject the idea that every one of them conveys the absolute truth. This is one of several kinds of human attitudes toward religion. They can be categorized as